PEMETAAN BIBLIOMETRIK DENGAN VOSVIEWER TERHADAP PERKEMBANGAN HASIL PENELITIAN IMPLEMENTASI GOOD CORPORATE GOVERNANCE - Arbi Abdul Kahfi; Muhammad Rizal; Tetty Herawati (LPPM University 17 Agustus 1945 Samarinda, 2022)
This study aims to determine the development map of research in the topic of implementation of good corporate governance (GCG). The study was conducted in October 2021 by conducting a search through the Scopus database. The search data is then analysis descriptively based on the year, name of the institution and country, the name of the journal, and productivity. The data is then analysis using the VOSViewer. The results showed that the number of publications of research results in this topic at Scopus in 2002-2021 had increased significantly. The largest publication of research results in this topic indexed in Scopus is Diponegoro University. The most productive researcher is Stiglbauer, M. Through network visualization shows that the development map of GCG implementation research is divided into 7 clusters with 22 topics. Density visualization shows the development of GCG implementation research has the heaviest weight on the word good corporate governance and corporate governance